2021
DOI: 10.15562/ism.v12i2.1006
|View full text |Cite
|
Sign up to set email alerts
|

Faktor risiko kejadian berat bayi lahir rendah di RSUP Sanglah, Denpasar, Bali, Indonesia

Abstract: Introduction:Maternal and child health has become a primary health focus in Indonesia and the maternal and child mortality rate in Indonesia is higher than those in South-East Asia countries. The incidence of Low Birth Weight (LBW) contributes to more than 50% of all neonatal mortality of all births in Indonesia. Therefore, identification of the risk factors that contributes to the incidence of LBW is important. Method: This retrospective case-control study involved 50 cases of LBW and 50 controls (baby with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…This finding aligns with the results of the study by Hanif et al [11], which showed that mothers with severe preeclampsia had 40 cases of LBW, while those without preeclampsia had 45 cases of LBW. Aryana et al's research [10] also supports these findings, confirming that a significant factor influencing LBW is maternal blood pressure. Each unit increase in maternal blood pressure increases the risk of LBW by 11.52 times.…”
Section: Hanif Et Al [11]mentioning
confidence: 70%
“…This finding aligns with the results of the study by Hanif et al [11], which showed that mothers with severe preeclampsia had 40 cases of LBW, while those without preeclampsia had 45 cases of LBW. Aryana et al's research [10] also supports these findings, confirming that a significant factor influencing LBW is maternal blood pressure. Each unit increase in maternal blood pressure increases the risk of LBW by 11.52 times.…”
Section: Hanif Et Al [11]mentioning
confidence: 70%
“…8 Semakin kecil umur kehamilan, maka berat lahir bayi juga semakin kecil karena secara fisiologis maupun anatomis organ yang ada di dalam tubuh janin belum berkembang secara sempurna sehingga risiko terhadap kesakitan bahkan kematian meningkat. 9,10 Umumnya bayi baru lahir memiliki berat badan berkisar 2500 gram sampai 4000 gram, bayi yang berat badan lahirnya <2500 gram disebut sebagai bblr. 11,12 Menurut World Health Organization WHO (2020) kematian oleh karena bblr di Indonesia mencapai 22.362 atau 1,32% dari total kematian.…”
Section: Pendahuluanunclassified